A new hybrid fuzzy ARTMAP and radial basis function neural network with online pruning strategy - Leow S.Y.; Wong S.Y.; Yap K.S.; Yap H.J. (Institute of Electrical and Electronics Engineers Inc., 2023)
E-learning; Functions; Fuzzy inference; Radial basis function networks; Fuzzy ARTMAP; Online learning; pruning; Radial basis functions; regression; Learning algorithms